Perancangan Sistem Informasi Penjualan Berbasis Website Pada HijabKu - Rindi Astuti; Moch. Hari Purwidiantoro; Sri Widiyanti (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
The development of information technology in the field of trade has grown very rapidly. Hijab is one of the needs of Muslim women, especially in Indonesia, which aims to cover their genitals. The growing trend of the current hijab is not intended to cover the private parts, but to become a style among women. Sellers must think ahead and be creative to create hijab models to make a profit, because currently the competition in the hijab business world is very tight. The method used in this study is the Rapid Application Development method. The purpose of the researchers using this method is to make the stages more structured. It was concluded that in designing this information system it was able to help the hijab selling process at the hijabku shop.